The European Union on the Verge of Bouncing Back in Macedonia - Markovikj, Nenad & Necev, Zoran (Konrad Adenauer Stiftung & IDSCS, 2018)
The case of Macedonia is a primer for EU’s credibility in the region. When the EU finally decided to engage, it helped the country recover after ‘approaching the edge of a cliff’3 and dismantle different (unlikely for the majority of citizens) scenarios for the future of the country that were floating in the air. This new momentum and energy is recognised and appreciated by the citizens, as reveals the IDSCS telephone survey conducted during December 2017, sampling 1100 respondents.4 The greater involvement of the EU in domestic political affairs (and post-crisis reforms) appears to have increased the Union’s credibility and visibility among Macedonian citizens. This also has resulted in a drop in the perception of Russian influence.
Keywords: Macedonia, EU, perceptions, confidence, partner